PROFITABILITY IN RASPBERRY PRODUCTION IN SERBIA - Veljković, Biljana; Petrović, Svetislav; Leposavić, Aleksandar; Glišić, Ivan (Economics of Agriculture, 2006)
Serbian position on the world market in raspberry production might be held only by obtaining the level in quality and quantity of production. The development of intensive raspberry production requires the application of modern technology for cultivating and growing raspberry orchards; also it is necessary to plan and keep records on costs and production economy. Level of profitability is mostly dependent on range of raspberry production and buy-out price and it can be increased by lowering production costs, increasing yield per area unit as well as by applying better organization of raspberry production and buy-out.